A Novel Adaptive Distance Protection Scheme Based on Variable Data Window - Deng, Xing; Yin, Xianggen; Zhang, Zhe; Wu, Dali (Elektronika ir Elektrotechnika, 2012)
The trip speed of traditional step mode distance protection with inverse time characteristics is quite slow when a short circuit fault occurs at the end of the protected line. To deal with this problem, a novel measured impedance convergence based inverse time distance protection is proposed in this paper. In this method, the convergence of measured impedance can dynamically reflect the level and attenuation degree of post-fault transient noise, and the method can adaptively decide the data window length of protective algorithm according to the result of real-time measured impedance convergence. More specifically, the faster the measured impedance convergence is, the shorter data window length of protective algorithm and the faster trip speed will be. Furthermore, a comprehensive adaptive variable data window distance protection scheme is established by using aforementioned two methods synthetically, which can overcome flaws of single method and efficiently improve trip speed of zone 1 of distance protection. Finally, the feasibility and effectiveness of the proposed scheme is proved with the simulation results. Ill. 8, bibl. 10, tabl. 4 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2365